Mechanical properties of cold sprayed Titanium and Nickel based coatings. Issue 1 (21st October 2015) - Silvello, A.; Cavaliere, P.
Abstract Cold spray is an innovative coating technology. Very fine particles are accelerated, then sprayed on a substrate in condition very far from material melting. The unique mechanical properties experienced by the sprayed material are due to the severe plastic deformation acting during particle impact. In the present paper, the microstructural and mechanical behavior of Ti‐ and Ni‐based nanocomposites coatings produced via cold spray are presented. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)